Predictors of personality and self-efficacy of sexual risk behavior in Mexican adolescents - Palacios, Jorge (Anales de Psicología / Annals of Psychology, 2018)
Background: This research determines the level of prediction of sensation seeking and self-efficacy on sexual risk behaviors in young Mexicans. The sensations seeking and self-efficacy have a combined impact on the risk sexual behaviors of young people. Method: The sensation seeking and selwef-efficacy were measured with two different scales in a non-probabilistic sample of 1012 young people, between 14 and 22 years old, from Mexico City. Results: showed that three facets of the sensation seeking and two dimensions of self-efficacy have a direct incidence in the sexual risk behavior of young people consistent with the postulated hypothesis and that in combination explain 19.2% of the variance. Conclusions: consider the combined effect of the search for sensation seeking and self-efficacy, as well as the practical implications for the development of preventive programs on sexual risk behavior in young people.